Supporting Change in Instructional Practices to Meet the Common Core Mathematics and Next Generation Science Standards: How Are Different Supports Related to Instructional Change? - Elaine Allensworth; Sarah Cashdollar; Amy Cassata (SAGE Publishing, 2022)
The Common Core State Standards in Mathematics and Next Generation Science Standards encourage substantial shifts in teaching, but how to enact change is not specified. This mixed-methods exploratory study shows how different implementation supports were related to teachers' use of standards-aligned instructional practices in the Chicago Public Schools. It provides comparative evidence that professional learning opportunities were strongly related to instructional practices, whereas curriculum and instructional resources had more modest and mixed relationships. In particular, collaboration with colleagues around instruction had consistently positive relationships with instructional practices in math and science, and these relationships were as strong among teachers who perceived many barriers to standards implementation as those who did not. We discuss implications for education leaders as they make decisions about how to best support teachers in standards-aligned math and science instruction.